Haematological changes and oxygen consumption in Oreochromis mossambicus exposed to sublethal concentrations of lead - James, R; Alagurathinam, S; Sampath, K (Indian Journal of Fisheries, 2011)
The effects of difTerent toxicants onhaematological parameters have been investigated(Goel and Kalpana 1985, lIaniffa et at.1986, Sampath et at. 1993) in fish. Studies onthe effect of metal toxicity on oxygen-carryingcapacity of blood and recovery of bloodcells from metal poisoning in fish,' however.are lacking. The present paper reports on thesublethal levels of lead on chosen bloodparameters and predicts the duration of completerecovery in Oreochromis mossambiicus